Whither relevance? Mathematics teachers' espoused meaning(s) of 'relevance' to students' everyday experiences - Nyabanyaba, Thabiso (My University, 2014)
This is a study of teachers’ espoused meaning(s) of ‘relevance’ as it refers to relating school mathematics tasks and activities to students’ everyday contexts. A qualitative approach was adopted, and a questionnaire and group interviews with teachers provided data on teachers’ ways of talking about ‘relevance’. The study focused on the inservice teachers in the Further Diploma in Education (FURTHER. DIPLOMA IN EDUCATION (FDE)) programme offered by the University of the Witwatersrand (Wits). The study analyses mathematics education literature about ‘relevance’, and Vygotsky’s (1979) and Lave’s (1991) theories as they illuminate learning as situated in socio-cultural contexts. The theories are not considered in terms of whether they provide “either-or” choices regarding relevance.Rather, they are considered in terms of some of the intricacies they reveal about relating school mathematics to students’ everyday experiences. Arising out of the teachers’ ways of talking about ‘relevance’ were concerns for improving students’ attitudes and perceptions towards mathematics. Persisting negative student attitudes are blamed on the way the teaching of mathematics has traditionally been isolated from the students’ everyday experiences. Also emerging are understandings that relating the learning of mathematics to students’ everyday experiences will induce positive associations for students. However, the teachers' discussions of the possible problems of relating math ematics to everyday experiences were limited to very obvious shortcomings such as this practice might be time-consuming. There were more complex understandings implicit in the teachers’ talk. This study has very important implications fdir those involved in curriculum development, especially the implementation of Curriculum 2005, as well as foi teacher educators. Continuing to propagate the value of a more ‘relevant’ teaching approach might now be of limited value.Emerging from this study is a suggestion that beyond a discourse advocacy of the ideals of Curriculum 2005 still lies the task of informing a more sophisticated understanding of ‘relevance’ in teachers, one dependent on a more practical exploration of situated tasks (relevant mathematics).